FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MAHASISWA AKUNTANSI TERHADAP PROFESI AKUNTAN PUBLIK (Studi Kasus Terhadap Mahasiswa Akuntansi Di Kota Bengkulu) - Zahrah Indah Ferina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Zahrah Indah Ferina; A Public Accountant is an accountant who provides services to obtain rewards or fees. The need for public accountants in the era of MEA is increasing, then the purpose of this study is to factors that affect the intention to the profession of Public Accountants. Factors influencing this intention with financial rewards and considerations of labor market. The sample used in this research is 83 respondents. Samples are obtained from accounting students who have completed the Auditing courses at State and Private University in Bengkulu. To analyze the hypothesis, this study used multiple regression analysis.The result of this research showed that financial reward and consideration of labor market has influence in career choosing as public accountant.Key words: Accounting Student, Intention, Public Accountant